Dogonyaro-Leaf-Extract as Inhibitor for Aluminum Corrosion in Acid - U Luvia, Ezeamaku; I Ochiagha, Eze; E Nkiru, Odimegwu; A Angela, Nwakaudu; S Amarachukwu, Okafor; Ifeanyi John, Obibuenyi; O Dominic, Onukwuli (Journal of New Developments in Chemistry, 2023)
Background of this paper investigates dogonyaro-leaf-extract as inhibitor for aluminum corrosion in 0.3-M hydrochloric acid, and its acceptability as original. In the methods, the extract was analyzed for phytochemicals and corrosion test performed on aluminum sheet before immersion in acid incorporated extract. Electrochemical Impedance Spectroscopy (EIS), tests were performed over frequency of 100 KHz–10 mHz and 10 mV peak to peak perturbation amplitude to obtain the corrosion potential. Tests were run at 30oC ± room temperature in aerated quiescent solutions. In weight loss method, coupons were suspended in aerated solutions before immersion in 20% mixture of sodium hydroxide and zinc dust to stop further corrosion. Morphology of the mirrorlike finished arid surface aluminum was measured with scanning electron microscope SEM. In the results, various phytochemicals were observed; significant effect of incorporating inhibitor on EIS data recorded and optimum extract efficiency was 99.46%, at 10 g/l, 60oC, within 6 hours. This result was validated and 99.3% efficiency obtained. Introduction of extract into acid corrodents caused increase of charge transfer resistance and reduced double layer capacitance. A warm arid clean coupon evolved after SEM test. In conclusion, there was increase in efficiency of inhibition as inhibitor concentration and temperature increased. Similarly, close responses towards the factors for Inhibition occur. Measured polarization showed that extract inhibited both cathodic and anodic reaction processes and thus, is classified as mixed type inhibitor. The investigations thus proved the extract as excellent corrosion inhibitor for aluminum in 0.3-M hydrochloric-acid.
Keywords: aluminum; corrosion; dogonyaro-leaf; extract; inhibitor